Comparative flavonoid profile of orange (Citrus sinensis) flavedo and albedo extracted by conventional and emerging techniques using UPLC-IMS-MS, chemometrics and antioxidant effects - Afifi, Sherif M.; Gök, Recep; Eikenberg, Ingo; Krygier, Dennis; Rottmann, Eric; Stübler, Anne-Sophie; Aganovic, Kemal; Hillebrand, Silke; Esatbeyoglu, Tuba (Frontiers in Nutrition, 2023)
Introduction: Citrus fruits are one of the most frequently counterfeited processed products in the world. In the juice production alone, the peels, divided into flavedo and albedo, are the main waste product. The extracts of this by-product are enriched with many bioactive substances. Newer extraction techniques generally have milder extraction conditions with simultaneous improvement of the extraction process. Methods: This study presents a combinatorial approach utilizing data-independent acquisition-based ion mobility spectrometry coupled to tandem mass spectrometry. Integrating orthogonal collision cross section (CCS) data matching simultaneously improves the confidence in metabolite identification in flavedo and albedo tissues from Citrus sinensis. Furthermore, four different extraction approaches [conventional, ultrasonic, High Hydrostatic Pressure (HHP) and Pulsed Electric Field (PEF)] with various optimized processing conditions were compared in terms of antioxidant effects and flavonoid profile particularly polymethoxy flavones (PMFs). Results: A total number of 57 metabolites were identified, 15 of which were present in both flavedo and albedo, forming a good qualitative overlapping of distributed flavonoids. For flavedo samples, the antioxidant activity was higher for PEF and HHP treated samples compared to other extraction methods. However, ethyl acetate extract exhibited the highest antioxidant effects in albedo samples attributed to different qualitative composition content rather than various quantities of same metabolites. The optimum processing conditions for albedo extraction using HHP and PEF were 200 MPa and 15 kJ/kg at 10 kV, respectively. Conclusion: Chemometric analysis of the dataset indicated that orange flavedo can be a valid source of soluble phenolic compounds especially PMFs. In order to achieve cross-application of production, future study should concentrate on how citrus PMFs correlate with biological engineering techniques such as breeding, genetic engineering, and fermentation engineering.